Feasibility and Effectivity of Video-Assisted Thoracoscopic Surgery (VATS) in the management of acute empyema thoracis - Haque, A K M Akramul (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Abstract not available J Bangladesh Coll Phys Surg 2024; 42: 119-120